Utilization of Corn Oil through Water Degumming Process for Lecithin Emulsifier Production - Fahmi Arifan; Muhammad Kelvin Nandita; Enrico Fendy Sapatra; Salsabila Salsabila (Universitas Gadjah Mada, 2021)
Lecithin is an emulsifier that plays an active role in reducing surface tension in making emulsions. The production of lecithin from other vegetable oils allows the use of other types of vegetable oil as a source of lecithin production to replace soy-based oil, which has begun to be used as a bioenergy raw material. This study aims to find an alternative source of new lecithin derived from corn oil by knowing the characteristics of lecithin and applied to mayonnaise. The resulting lecithin was used in mayonnaise with a 2 factorial randomized block design method consisting of 3 levels. Based on the results obtained, the characteristic of corn oil lecithin is that the largest content is hexadecanoic acid which is 44.79%, and the strongest vibration band is CH2 vibration with stretching modes of symmetry and asymmetry at 2922 and 2853 cm–1 and the terminal CH3 group in the 1374 cm–1. L3C3 treatment was the best result with 60% fat content, 4% emulsion stability, 2.12 cP viscosity, and 1.42 × 10–3 N/m surface tension and organoleptic showed a preference value, namely color 4.4 (like), taste 3.2 (sufficient like), smell 4 (like), and texture 3.80 (like it).